The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.ejso.2021.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Risk of metachronous peritoneal metastases in patients with pT4a versus pT4b colon cancer: An international multicentre cohort study

Abstract: Introduction: With evolving treatment strategies aiming at prevention or early detection of metachronous peritoneal metastases (PM), identification of high-risk colon cancer patients becomes increasingly important. This study aimed to evaluate differences between pT4a (peritoneal penetration) and pT4b (invasion of other organs/structures) subcategories regarding risk of PM and other oncological outcomes. Materials and methods: From eight databases deriving from four countries, patients who underwent curative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 26 publications
5
27
4
Order By: Relevance
“…Compared with T3 tumors, T4 tumors had a higher proportion of mPC; T4 tumors were regarded as "low risk PC" in a recent study, 15 and the risk of recurrent PC in patients with T4 tumors was only lower than that in patients with synchronous peritoneal or ovarian metastasis at the initial radical surgery. Several studies 17,21 have found that T4a stage cancer had much higher risk for PC after radical colon cancer resection compared with T3 and T4b stage cancer, but we did not find this in our present study (pT4b vs. pT4a, HR = 0.704, p = 0.343). However, the incidence of mPC in T4a was slightly higher in this cohort, the small number of T4 patients may be the reason for the lack of statistical difference.…”
Section: Risk Factors For the Development Of Mpccontrasting
confidence: 99%
See 4 more Smart Citations
“…Compared with T3 tumors, T4 tumors had a higher proportion of mPC; T4 tumors were regarded as "low risk PC" in a recent study, 15 and the risk of recurrent PC in patients with T4 tumors was only lower than that in patients with synchronous peritoneal or ovarian metastasis at the initial radical surgery. Several studies 17,21 have found that T4a stage cancer had much higher risk for PC after radical colon cancer resection compared with T3 and T4b stage cancer, but we did not find this in our present study (pT4b vs. pT4a, HR = 0.704, p = 0.343). However, the incidence of mPC in T4a was slightly higher in this cohort, the small number of T4 patients may be the reason for the lack of statistical difference.…”
Section: Risk Factors For the Development Of Mpccontrasting
confidence: 99%
“…Patients with an advanced T stage tumor were found to be at increased risk for developing mPC, which has been demonstrated previously. [11][12][13][14][15][16][17][18][19][20][21] In this study, the incidence of mPC of T3, T4a, and T4b was 6.3%, 25.0%, and 19.1%, respectively. Compared with T3 tumors, T4 tumors had a higher proportion of mPC; T4 tumors were regarded as "low risk PC" in a recent study, 15 and the risk of recurrent PC in patients with T4 tumors was only lower than that in patients with synchronous peritoneal or ovarian metastasis at the initial radical surgery.…”
Section: Risk Factors For the Development Of Mpcmentioning
confidence: 67%
See 3 more Smart Citations